(untitled) (Global Scientific Review, 2026)
This research provides a broad analytical assessment of the relevance of financial technology (FinTech) as an essential mechanism for fostering innovation in finance. It finds that FinTech is an all-encompassing, transformative ecosystem that disrupts conventional financial services, processes, and business models by delivering personalized services; increasing operational efficiency through smart devices; facilitating alternative financing channels; and striving for financial inclusion. The study also draws attention to the interconnected challenges of actualizing this emerging role, above all, lagging legislation , cybersecurity threats, and the digital and institutional divide. It stresses the need not only to address these challenges, but also to create an enabling environment built on three pillars: flexible, smart regulation (regulatory sandboxes); strategic investment in digital infrastructure and human capital; and incentivizing constructive coordination among all players in the financial ecosystem. Arab experiences in FinTech analysis. It is clear from Arab experiences that the successful application of FinTech as an innovation driver depends on a welldefined national vision and a strong enabling environment. To support this, the study concludes with a series of practical recommendations that leverage FinTech ’s innovative potential and turn these into concrete proposals to support the creation of a more flexible, inclusive, and competitive Arab financial sector in the new digitalbased global economy.